(untitled) (International Journal of Engineering and Computer Science, 2023)
In the automotive domain, the trend of ECUs becoming central units facilitating deployment of functionalities sliced up across domains and their interlinking makes MC soberly complex. Some typical functionalities, as examples, are driven control and safety, electrification of the powertrain, and driving assistance. This phenomenon also led to a sharp increase in testing these MCs. Incidents such as those recently seen in highly and fully automated driving automobiles show that rigorous testing of such MCs for readiness to be released to the field is an exponentially increasing challenge. To cope with the MC wiring complexity and its handling efforts, hardware-in-the-loop testing devices are increasingly used to test MC software functionality. Incidentally, many MC customers often first test dumps of the MC software in their software integration labs or they use simulators known as models. The challenges of increasing the number of test cases to pass for the release candidate and the amount of test runs are similar.